Menandro e l'evoluzione della commedia greca Atti del convegno internazionale di studi in memoria di Adelmo Barigazzi nel centenario della nascita (Firenze, 30 settembre - 1 ottobre 2013) - Casanova, Angelo Alfredo (Firenze University Press, 2014)
The volume contains eighteen original essays, written - upon invitation - by internationally renowned scholars from various Italian or foreign universities. The major issues that recent papyrus discoveries have raised (or re-proposed) on the text and interpretation of several of Menander's comedies are addressed, outlining an authoritative and fully updated picture of our knowledge in this regard. Among other things, the first fruits of the edition (with photography) of a new, previously unpublished fragment of the famous (and discussed) Michigan papyrus are offered. All reports present remarkable aspects of editorial novelty, with philological, linguistic and literary comments, relevant for the cultural debate on Menandro's comedy, and therefore for the history of ancient theater and its evolution, as well as for the study of the influences exercised from the New Comedy on the later Latin and Italian tradition.